UKRAINIAN WOMEN'S SELF-PRESENTATION IN SOCIAL MEDIA DURING FORCED MIGRATION: THE EXPERIENCE OF WAR (Psychology Travelogs, 2024)
The article examines the digital self-presentation strategies of Ukrainian women on social media platforms during forced migration due to Russian aggression. Based on a mixed-methodology approach combining digital ethnography, visual sociology, and feminist methodology, the study analyzed 200 social media profiles and conducted 30 in-depth interviews with Ukrainian women who were forced to leave the country after February 24, 2022.The research identified four dominant self-presentation strategies: patriotic (34.2%), adaptive (23.7%), community-oriented (22.1%), and professional (20%). The dominance of the patriotic strategy indicates a high level of national consciousness and cultural identity preservation even while abroad. A significant transformation of digital identity was observed through the conscious strengthening of national markers in social networks and active use of bilingual content (78% of profiles), reflecting simultaneous desires to maintain connections with Ukraine and integrate into new environments.The emotional aspect of self-presentation demonstrates complex dynamics: positive narratives about successful adaptation prevail (73% of profiles), while there is also a distinct tendency toward nostalgic content (58% of profiles), especially related to national holidays and family events. Social networks have become an effective tool for forming and maintaining diaspora communities, with a high level of emotional solidarity (82% of posts contain elements of mutual support).The study reveals the maintenance of strong emotional connections with Ukraine: 91% of respondents regularly express their concerns about events in their homeland, indicating the formation of transnational identity in digital space. The research findings have practical implications for developing support programs for Ukrainian migrants and can be utilized in forming social integration policies in host countries.
Keywords: digital self-presentation; refugee; Ukrainian women; social media; cultural identity; diaspora communities; digital ethnography